Revitalization of Islamic Education in Shaping Student Character at Islamic Boarding School Asshiddiqiyah 2 Tangerang - Halimahtusa’diah, Halimahtusa’diah; Syarif, Fajar; Al Ghifary, Muh. Ubaidillah (YASIN, 2025)
Character-based Islamic education, until now, is still essential when the moral degradation of the nation's children continues to increase from year to year. This research aims to reveal the revitalization of Islamic education and how it shapes student character at Islamic Boarding School Asshiddiqiyah 2 Tangerang. Researchers used a qualitative approach with a case study type. The results showed that the boarding school had revitalized character-building through Islamic education by formulating the achievement of character-building goals according to the needs of the times and strengthening positive habituation in daily activities based on Ahlussunnah Wal Jama'ah values (tawasuth, tidal, tasamuh, tawazun, amar ma'ruf nahi munkar). The results of this revitalization can be seen in the presence of students who optimize their potential through value transformation, value transactions, and value internalization in their daily lives.